2013
DOI: 10.3415/vcot-11-11-0154
|View full text |Cite
|
Sign up to set email alerts
|

Experiences using the Fixin locking plate system for the stabilization of appendicular fractures in dogs

Abstract: Despite a modest complication rate, the Fixin locking bone plating system appears to be an acceptable choice of implant for the stabilization of appendicular fractures in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 23 publications
6
32
0
1
Order By: Relevance
“…In a retrospective clinical study evaluating the use of Fixin plates in dogs, implant failure occurred in 7 of 82 stabilized fractures. 11 The majority of the fractures were stabilized with the mini Fixin plate system which is the plate series that was evaluated in the current study. The implant failures that occurred in these dogs were characterized by screw breakage (n ¼ 2), plate breakage (n ¼ 4) and plate bending (n ¼ 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a retrospective clinical study evaluating the use of Fixin plates in dogs, implant failure occurred in 7 of 82 stabilized fractures. 11 The majority of the fractures were stabilized with the mini Fixin plate system which is the plate series that was evaluated in the current study. The implant failures that occurred in these dogs were characterized by screw breakage (n ¼ 2), plate breakage (n ¼ 4) and plate bending (n ¼ 1).…”
Section: Discussionmentioning
confidence: 99%
“…2,[7][8][9][10] The conical coupling locking plate system (Intrauma FIXIN; Rivoli, Italy) has been used to successfully stabilize diaphyseal tibial fractures in dogs. 11 This system has a conical bushingscrew head locking mechanism which confers fixed angle stability without altering the plate's thickness. 12 Benefits ascribed to the thin plate profile include ease of contouring, facilitating minimally invasive plating osteosynthesis application and maintenance of implant elasticity that stimulates callus formation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, the use of locking plates in the stabilisation of periarticular fractures has gained popularity in the treatment of these fractures in humans . Locking plates utilise a variety of different locking mechanisms to create angle‐stable constructs, whereby the screw head engages with the plate screw hole, and have been reported in the veterinary literature for successful stabilisation of many different fractures and osteotomies . The number of screws required in each fragment is still not clearly defined; however, it has been suggested that adequate stability can be achieved with a minimum of two locking screws per fragment, which may prove advantageous when stabilising small bone fragments.…”
mentioning
confidence: 99%